Determination of trace sodium cyclohexyl sulfamate in Baijiu by HPLC - WEI Gong, WANG Le, LI Chunfang, ZHANG Zhiyang, REN Guojun, YAN Wei, WANG Hui (Zhongguo niangzao)
A method for the determination of trace sodium cyclamate in Baijiu by HPLC was established. According to the thermal stability of sodium cyclamate, the Baijiu samples were concentrated for the first time, extracted by different solvents after derivatization, and then the samples were concentrated twice after extraction with different extraction solvents and alkali washing. After resolubilization with different solvents, the chromatographic conditions were optimized by mobile phase test, the pretreatment conditions were optimized by single factor tests and orthogonal tests, and then evaluated by methodological investigation. The results showed that the optimal pre-treatment conditions were as follows: weighing sample 100 g, concentrating in boiling water bath, drying and steaming for 0.5 h to remove most of the interfering components in Baijiu, extracting with n-heptane after derivatization, secondary concentrated after alkali washing, and determined by liquid chromatography after mobile phase resolubilization. The results showed that the linear relationship of the standard curve of the method was good in the range of 0.01-1 mg/kg (R2=0.999 8), the detection limit was 0.01 mg/kg, and the quantification limit was 0.03 mg/kg. The recovery rate of sodium cyclamate in different flavor Baijiu samples was 94.4%- 103.7%, and the relative standard deviation (RSD) of precision test results was 2.70%-3.73% (n=6). The method had high accuracy and good precision, which was suitable for the determination of trace sodium cyclamate in various flavor Baijiu.